TRANSFORMASI LAYANAN PERPUSTAKAAN BERBASIS MEDIA SOSIAL DALAM MEMENUHI KEBUTUHAN INFORMASI KELOMPOK MILENIALS - Wafi Ariqo; Yunus Winoto (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
The development of information technology has greatly affected people's lives. This can be seen with theuse of gadgets that cannot be separated from one's activities in daily life. In addition, one of the othercharacteristics is the emergence of new media platforms in the community, namely social mediaplatforms. In this regard, the library must always exist in a society that is always dynamic, so that libraryinstitutions follow developments around them and are able to transform services according to the needsof the community, especially the millennial group. implementing social media-based library services.This paper tries to discuss about the transformation of social media-based services. The method used islibrary research method. From the results of the study, it is known that the transformation of libraryservices based on social media is something that must be done in an effort to meet the informationneeds of the community, especially people from the millennial group. This is because social media hasseveral characteristics such as networking, information, interaction, dissemination and entertainmentelements that are in line with the expectations of the millennial group.